Análise ambiental da área do Morro do Cuscuzeiro (Analândia, SP) como subsídio ao planejamento do ambiente local - Leite, Samantha de Souza (Universidade Federal de São Carlos, 2002)
The principal aim of this work was to supply information to support the environmental planning focused in the minimizations of the environment degradation around Cuscuzeiro Hill (Analândia, SP). For this purpouses, maps of the area were elaborated resulting on a reorganization purpose to landscape uses. The soil and vegetation of the Cuscuzeiro Hill forest were characterizaded and the trails to reach the Cuscuzeiro Hill were mapped ti support a reorganization purpose. The map analyses showed a high potencial risk to the superficial erosion, because of the association of sand solis and grass areas with high slopes. The natural vegetation of such areas should be recomposed to decrease the superficial erosion risk. In general, the Cuscuzeiro Hill trails are not safe enough in some parts, besides to have a difficult access to the tourists, specially because of the high slopes. This work evidenced factores that could degrade either the trails or the whole environment. The reorganization of the trails is needed either to avoid the environment degradation or to improve their use conditionals. The vegetation characterization found 67 species, 51 genera and 27 families in the Cuscuzeiro Hill forest. A significant difference were found between two regions around the Cuscuzeiro Hill based on the heigh and diameter of the trees. The major parte of the Cuscuzeiro Hill soil is composed by sand. This vegetation is probably not supported only by the nutrients of the soil, since it is very depleted, and the litter may supply na important input to the planths growth and maintance.
Keywords: Planejamento físico - ambiental; Florística; Sistema de informação geográfica; Solos - erosão; Trilhas; Environmental planning; Floristic; Geographic information system; Soil - erosion; Footpath; CIENCIAS BIOLOGICAS::ECOLOGIA